2019
DOI: 10.1037/str0000067
|View full text |Cite
|
Sign up to set email alerts
|

Overtime and quality of working life in academics and nonacademics: The role of perceived work-life balance.

Abstract: While academic jobs generally provide a good degree of flexibility, academics also tend to work extra hours which can then lead to a poorer work-life balance. In this study, we compare academic vs. non-academic staff and anticipate that academics will generally report a poorer Quality of Working Life, a broad conceptualization of the overall work experience of employees. Secondly, we investigate whether the negative relationships between being an academic and Quality of Working Life variables are made worse by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 50 publications
(97 reference statements)
5
64
1
2
Order By: Relevance
“…Our study revealed a number of variables that scholars have instigated, including, but not limited to, self-efficacy, empowerment, emotional intelligence, spirituality, job satisfaction, self-confidence, transformational leadership, work-related quality of life and work engagement. Investigating these variables is consistent with other literature highlighting the need to consider a range of factors to ascertain how mental health is being influenced by personal and environmental factors(Fontinha, Easton, & Van Laar, 2019;Hall, Johnson, Watt, Tsipa, & O'Connor, 2016).…”
supporting
confidence: 81%
“…Our study revealed a number of variables that scholars have instigated, including, but not limited to, self-efficacy, empowerment, emotional intelligence, spirituality, job satisfaction, self-confidence, transformational leadership, work-related quality of life and work engagement. Investigating these variables is consistent with other literature highlighting the need to consider a range of factors to ascertain how mental health is being influenced by personal and environmental factors(Fontinha, Easton, & Van Laar, 2019;Hall, Johnson, Watt, Tsipa, & O'Connor, 2016).…”
supporting
confidence: 81%
“…University teachers hold numerous responsibilities in their role, including teaching students, conducting and publishing research, as well as completing administrative tasks. When combined with additional characteristics of the profession such as working significant overtime hours (Fontinha et al, 2019) and having fixed-term employment contracts (Higher Education Statistics Agency, 2018), it is not surprising that university teachers are considered at-risk for compromised well-being (Kinman and Johnson, 2019). This has also been recognized by, among others, the German Research Foundation, the Dutch Research Council, the Royal Netherlands Academy of Arts and Science, and the Association of Universities in the Netherlands (Rijksoverheid, 2019;Nederlands Wetenschappelijk Onderzoek [NWO], 2020).…”
Section: Teacher Well-beingmentioning
confidence: 99%
“…However, and fortunately for workers, WLB is becoming a trendy topic in recent years [19] in the personal sphere and also in the organizational context [20]. Although the sectors studied are diverse, recent studies on the topic focus on health [21][22][23][24], transport [25], or education [26,27]. The study of WLB is specifically prominent in the field of public health [3].…”
Section: Introductionmentioning
confidence: 99%